Acute pneumococcal myelitis in an adult patient - Klaudija Višković; Matej Mustapić; Marko Kutleša; Dragan Lepur (Journal of Global Infectious Diseases, 2014)
Pneumococcal meningitis represents the most severe community-acquired bacterial meningitis. The disease is frequently associated with various complications. We present a case of pneumococcal meningitis in an immunocompetent adult patient treated with hypothermia. The disease course was complicated with severe myelitis and consequent paraplegia which is an extremely rare complication of pneumococcal disease.